AN ANALYSIS OF CODE SWITCHING AND CODE MIXING IN DEAR LOVE FILM BY DEDY SYAHPUTRA - Budik Kusworo (IAI Al-Qolam, 2022)
By communicating we use a language that can be understood by the interlocutor or listener, Therefore, the most fundamental language function is to serve as a medium of communication, socialization, and relationship from one to another, so that a social system or a society might be established. The phenomenon of code switching and code mixing has long intrigued scholars who have researched what triggered the incident. The phenomenon of code switching, and code mixing has become a trend or language style in society, especially among young people. They are very familiar with code switching or mixing in their speech. In addition to young people and even older people, many of them use code-mixing languages and code switching, this is already familiar to us. This phenomenon also appears in the film the researcher studied under the title